The Influence of Entrepreneurship Education and Family Support in Strengthening Entrepreneurial Values among Students of State Vocational High School 2 Jombang - Maya Anjelina Agustin; Agus Prianto (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The high unemployment rate among vocational high school graduates underscores the need to strengthen entrepreneurial values as part of career preparation. This study aims to analyze the influence of entrepreneurship education and family support on the entrepreneurial values of students at SMK Negeri 2 Jombang. A quantitative approach with a causal-associative design was employed. The sample consisted of 135 students selected through proportional random sampling. Data were collected using questionnaires and analyzed using multiple linear regression. The findings indicate that entrepreneurship education and family support have positive and significant effects on students’ entrepreneurial values, both partially and simultaneously. Family support was identified as the most dominant factor influencing entrepreneurial values, while the two variables collectively explained 43.7% of the variance in entrepreneurial values. These findings suggest that entrepreneurial values among vocational students are strengthened through the synergy between formal entrepreneurship education and supportive family environments. This study concludes that the development of creative, independent, innovative, and responsible entrepreneurial characteristics requires collaborative efforts between schools and families. The findings contribute to the literature on vocational entrepreneurship education and provide practical implications for strengthening school–family collaboration in fostering entrepreneurial character among vocational students.